Transformasi Sistem Lembaga Pendidikan Islam di Patani-Thailand Selatan - Ruslan Rasid; Abdul Munip; Hilman Djafar (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
This study aims to analyze the organization of the Islamic education system which aims to analyze the Muslim community in Patani-Thailand. The research methodology used in this study is qualitative-descriptive. The results showed that the transformation of the Islamic education system in Patani started from: First, the mosque or surau system. In the early days of Islam, this mosque / surau system was a place for